STANDING ISSUES OF RUSSIAN BANKS AND SOLUTIONS - Т. Ю. Мазурина (Вестник университета)
The article deals with current issues of today, hampering the development of the Russian banking sector, such as the availability of banking services in the regions, low capitalization of banks formed imperfect structure of the banking system and a number of others. The arguments justifying the need to create favorable conditions for the expansion of the presence of banks in the region, preservation of credit institutions with little capital, to restore the role of the banking sector in the mechanism of transformation of savings in the production of investment. There are basic directions of solving the above problems.